183k views
12 votes
5x -9y =-26
-2x +3y =11​

2 Answers

4 votes

Answer:

x= -7

y= -1

Explanation:

5x-9y= -26..............(1)

-2x+3y= 11...............(2)

5(-2x+3y= 11)

-10x +15y = 55................(3)

2(5x-9y= -26)

10x-18y= -52.....................(4)

Add equation 3&4

-10x+15y= 55

10-18y= -52

-3y= 3

y= -1

put y= -1 into equation ............(3)

-10x+15y= 55

-10x+15(-1)= 55

-10x-15 = 55

-10x= 55+15

-10x= 70

x= -7

Therefore;

x= - 7 and y= - 1

User Unorsk
by
5.2k points
7 votes

Answer:

(-7, -1)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtract Property of Equality

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

5x - 9y = -26

-2x + 3y = 11

Step 2: Rewrite Systems

-2x + 3y = 11

  1. Multiply everything by 3: -6x + 9y = 33

Step 3: Redefine Systems

5x - 9y = -26

-6x + 9y = 33

Step 4: Solve for x

Elimination

  1. Combine 2 equations: -x = 7
  2. Divide -1 on both sides: x = -7

Step 5: Solve for y

  1. Define equation: 5x - 9y = -26
  2. Substitute in x: 5(-7) - 9y = -26
  3. Multiply: -35 - 9y = -26
  4. Add 35 on both sides: -9y = 9
  5. Divide -9 on both sides: y = -1
User Pedro Vicente
by
4.1k points